INTEGRASI WAHYU DAN AKAL DALAM PENDIDIKAN ISLAM KAJIAN EPISTIMILOGIS UNTUK PENGEMBANGAN KURIKULUM - Sudirmanto Sudirmanto; St Nurhayati; Nur Aliah (STKIP Pesisir Selatan, 2026)
Knowledge in the Islamic perspective is derived from revelation and reason, which should be understood as an integrated epistemological unity. However, in contemporary Islamic education practices, a separation between the two remains evident, particularly in curriculum development, resulting in learning processes that do not fully reflect the integration of revelatory values and rational reasoning. This study aims to examine the epistemological integration of revelation and reason as a foundation for the development of the Islamic education curriculum, including the formulation of educational objectives, the development of curriculum content, and the selection of instructional methods. This research employs a qualitative approach using a library research method, drawing upon primary and secondary sources in the form of scholarly works, journal articles, and contemporary books relevant to Islamic educational epistemology and curriculum development. The data are analyzed through content analysis techniques, emphasizing the conceptual interrelationships between revelation, reason, and curricular practices. The findings indicate that the integration of revelation and reason can be formulated as an applicable epistemological framework that guides the formulation of holistic educational objectives, the development of integrative curriculum content, and the implementation of contextual and reflective learning methods.